Функційне навантаження градації оцінних значень у портретних описах жінки (на матеріалі творів сучасної української жіночої прози) - Шевчук, З. (Культура слова, 2020)
Стаття присвячена аналізові оцінного значення мовних одиниць
шляхом з’ясування функційного навантаження аксіологічних мовних
маркерів на шкалі градації в портретних описах жінки. Установлення
зв’язку між оцінним значенням мовних одиниць та ознакою,
вираженою більшою чи меншою мірою, виявляє градацію, виражену в
семантичній структурі окремого слова. Дослідження градації оцінки
на рівні тексту уможливлює з’ясування поступової зміни оцінних
значень мовних одиниць. Засоби на позначення зовнішності та
внутрішніх характеристик відображають специфіку оцінного акту
і сприйняття зовнішності людини за допомогою їхньої візуалізації у
суспільній свідомості. The article attempts to analyze the estimated value of language units by
finding out their functional load on the gradation scale in woman’s portrait.
The interpretation of the key concepts “portraiture”, “rating scale” is given.
Due to the broad approach to modeling of woman’s portrait in fiction,
the concept of “gradation” as a category that reproduces the positive /
negative attitude to the object and, accordingly, its movement on the scale
of general evaluation is proposed to interpret. The main markers of the
expression of gradation in woman’s portrait descriptions are adjectives,
adverbs, pronouns, which has been found. They intensify or de-intensify
the meaning on the scale of traditional (established) antinomies. The role
of color names on the gradation scale is determined (to characterize the
hair of a woman with a red nucleus). The gradation of the estimated value
of language units in other descriptions of the internal state, the character
of a woman (mostly with negative values) is reproduced. The gradation
series of nomenclatures is demonstrated, in which the process of formation
of original paraphrased nominations is traced.